It takes two to tango: Linking signature strengths use and organizational support for strengths use with organizational outcomes - Tahira Mubashar; Claudia Harzer (Journal of Occupational and Organizational Psychology, 2023)
The present study tested and extended the motivational process of the Job Demands-Resources (JD-R) theory to explicate the role of signature strengths use as a personal resource and organizational support for strengths use as a job resource for a host of organizational outcomes. Our greater interest was to examine serial and parallel mediation of employee-level variables (i.e., work engagement, job performance, and turnover intentions) between both types of resources (personal and job) and organizational outcomes (i.e., organizational performance and turnover). We collected data from 202 top managers from 56 branches of a large bank in Pakistan. The participants filled in data for most of the study variables, whereas the concerned bank officials provided objective ratings of organizational performance and turnover. The results indicated the indirect effect of signature strengths use and organizational support for strength use on perceived and objective organizational performance mediated by work engagement, job performance, and turnover intentions. Signature strengths use also showed a direct effect on perceived and objective organizational performance. The findings illustrate the potential benefits of using one's signature strengths for employee and organizational success and reiterate the importance of enhancing organizational support for strengths use for management groups who in turn can contribute substantially to organizational performance.
Keywords: 650; job demand-resource theory; job performance; job resource; organizational performance; organizational support for strengths use; personal resource; signature strengths use; turnover; turnover intentions; work engagement